(untitled) (Research, Society and Development, 2023)
Diabetes is one of the main risk factors for periodontitis. Although the relationship between diabetes and periodontitis is well understood, there is still a lack of studies that establish the risk of this relationship among frail and non-frail elderly people. The objective of this case-control study is to evaluate the risk relationship between hyperglycemia and periodontal disease in elderly patients. This case-control study approached 20 elderly people who were treated at a Family Health Unit in the city of Rio Branco – Acre. 12 men and 8 women were included, divided into two groups: 6 were included in the group of people who had fasting plasma glucose ≥ 126mg/dl and 14 included in the group of people who had fasting plasma glucose less than 120mg/dl. In the case group (hyperglycemic), 6 patients were diagnosed with periodontitis and in the control group, no patient presented periodontal disease. In this study, 8 patients were classified as frail and 12 patients classified as not frail. Fasting plasma glucose ≥ 126m g/dl increase the risk of periodontitis 2.9 more than if fasting plasma glucose levels were below 126mg/dl (95% CI). When an elderly person is frail, there is an 18 times greater risk of being diagnosed with periodontal disease compared to a non-frail elderly person. It is essential that dentistry professionals establish sizing methods for better health care for diabetic elderly people and health policies should be aimed at strengthening dental care for frail people.